1999
DOI: 10.1063/1.369758
|View full text |Cite
|
Sign up to set email alerts
|

Possible solution to the problem of high built-up stresses in diamond-like carbon films

Abstract: The various issues relating to the nature of high built-up stresses in diamond like carbon (DLC) films are presented and analyzed and the utility of pulse plasma technique in growing low residual stress DLC films is emphasized. Subsequently, sufficiently thick (2.2 μm) and hard (2000 kg/mm2) DLC films of significantly low stress (≈0.1 GPa) were deposited by the pulse plasma enhanced chemical vapor deposition (PECVD) technique. Stress values were found to be less than 0.5 GPa even with wide variation in pulse p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 63 publications
(28 citation statements)
references
References 51 publications
2
26
0
Order By: Relevance
“…Moreover, initially a film thickness of 150 nm (10,000 pulses) was targeted and yielded an actual film thickness of 110 nm, as determined by profilometry. However, this coating was not adhesive and tended to buckle and peel off easily indicating a high degree of internal stress in the film, which agrees with results published by Kumar [44]. When the target film thickness was lowered to 60 nm (5,000 pulses), pinhole free coatings were obtained.…”
Section: Deposition Of Dlcsupporting
confidence: 88%
“…Moreover, initially a film thickness of 150 nm (10,000 pulses) was targeted and yielded an actual film thickness of 110 nm, as determined by profilometry. However, this coating was not adhesive and tended to buckle and peel off easily indicating a high degree of internal stress in the film, which agrees with results published by Kumar [44]. When the target film thickness was lowered to 60 nm (5,000 pulses), pinhole free coatings were obtained.…”
Section: Deposition Of Dlcsupporting
confidence: 88%
“…It appears that one can obtain thick a-C:H films with a multilayer structure of Cu/a-C:H, because interfacial layers present in the multilayer structure reduce the residual compressive stress in the films as the soft/hard structure provides the needed relaxation in the overall structure. The pulsed plasma grown soft/hard DLC layer and Si containing DLC multilayer structure concept for the relaxation of the residual stress has been reported by Kumar et al [26,27]. The soft Cu layer present in the multilayer structure acts as a metallic substrate for subsequent a-C:H layers and prevent the delamination of the multilayer structure.…”
Section: Residual Stressmentioning
confidence: 93%
“…32,33 However, the generation of high compressive stress is one of the mechanisms proposed for the growth of high sp 3 bonded DLC films. 34 Ferrari et al, 35 on the other hand, suggested that it is not only the stress that influences the sp 3 carbon bonding and vice versa but also that stress can be manipulated by rearranging the sp 2 C phase.…”
Section: Resultsmentioning
confidence: 99%